Actions to prevent sexual violence against adolescents: an integrative literature review - Alejandra Isabel Vargas Rivera; Edna Johana Mondragón-Sánchez; Fatima Karine Apolonio Vasconcelos; Patricia Neyva da Costa Pinheiro; Adriana Gomes Nogueira Ferreira; Marli Teresinha Gimeniz Galvão (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: to identify actions to prevent adolescent sexual violence. Method: an integrative literature review of five databases, Medline/Pubmed, Scopus, Lilacs, Bdenf, Cinahl using the following descriptors "adolescent" "adolescence" "youth" "primary prevention" "prevention" "primary" "sexual violence", plus the Boolean operators AND and OR, with a final sample of 24 articles; the evidence was assessed by the Grading of Recommendations Assessment, Development and Evaluation Results: the review identifies different structures of the study object, classified in the categories "Interventions with programs created by authors" and "Interventions with standard programs". Conclusion: there are actions to prevent sexual violence against adolescents; the participants' knowledge was assessed immediately after the intervention, but the assessment of the participants' acquisition of habits and behavioral changes was to a lesser extent; health prevention is crucial for society's healthy development, which demonstrates that its applicability in the environment directly favors human health.